Coronary Artery Disease: Its Etiology, Epidemiology, Clinical Course And Modern Methods Of Treatment (Eurasian Medical Research Periodical, 2024)
This article is about the treatment of patients with coronary artery disease. The article discusses the types of coronary artery disease, its causes, complications observed in patients with the disease, measures to prevent them, its etiology, epidemiology, clinical course, and modern methods of treatment.